Penanganan Tuberkulosis Resistan Obat pada Daerah Terpencil: Mission Impossible? [Management of Drug-Resistant Tuberculosis in Isolated Area: Mission Impossible?] - Ivan Banjuradja; Asep Purnama (Faculty of Medicine Universitas Airlangga, 2017)
Background: Complicated drug-resistant Tuberculosis (TB) management becomes a distinctive challenge for health care provider in rural area. Case: We reported 6 drug-resistant TB cases that were found in Sikka Regency, East Nusa Tenggara, based on rapid molecular test. Each case had unique problem which needs specific management, such as difference between the conventional and rapid drug susceptibility test, appearance of second line injection drug resistant (Pre-XDR TB), Human Immunodeficiency Virus (HIV) co-infection, emergence of serious acute psychosis side effect, and the drop out management. Discussion: We will discuss the management of each individual’s problem that arises during the antitubercular treatment monitoring and the requiring regimen modification under the national guideline. Conclusion: Drug-resistant TB management is a very complex matter. However, with sustainable effort, commitment, and collaboration between referral center and health care provider in rural area, guidelin be appropriate management could be achieved. Despite its possibility, prevention of resistant TB should have been done as early as possible, one of them is completion of regular TB treatment.